Kajian Yuridis terhadap Produksi Minuman Fermentasi Khas Bali yang Tidak Memiliki Izin Edar - Nyoman Satria Bismantara; Ida Ayu Putu Widiati; I Wayan Arthanaya (Jurnal Preferensi Hukum, 2022)
Currently, there is a rampant circulation of Balinese fermented drinks that do not have distribution permits. The Government of Indonesia has regulated regulations related to the circulation of fermented beverages that do not have a distribution permit in Presidential Regulation No. 74 of 2013 and Bali Provincial Governor Regulation No. 1 of 2020. Therefore, the purpose of this reserach is to examine the legal arrangements regarding the production of Balinese fermented drinks and to analyze law enforcement against Balinese fermented beverage business actors without a distribution permit. This reserach uses a normative legal research type, using a statutory approach and a conceptual approach. The sources of legal materials for this research are: primary, secondary and tertiary sources of legal materials. This research data collection technique is a literature reserach technique, namely by reviewing legal materials that intersect and then being categorized or classified and archived, written, quoted, summarized, investigated as needed with a qualitative approach. The researcher found that Legal arrangements regarding the production of Balinese fermented beverages are regulated in Bali Provincial Governor Regulation No. 1 of 2020. Bali Governor Regulation No. 1 of 2020 is a supporting factor for law enforcement because it is a reference for the law in addition to law enforcement factors, namely police officers in this case pamong praja police who have the task of supporting in organizing local government in the field of security and order and enforcement of local regulations in terms of controlling the circulation of alcoholic beverages.